2021
DOI: 10.3389/fpsyg.2021.659994
|View full text |Cite
|
Sign up to set email alerts
|

Smart Speaker Recommendations: Impact of Gender Congruence and Amount of Information on Users' Engagement and Choice

Abstract: The relevance of smart speakers is steadily increasing, allowing users perform several daily tasks. From a commercial perspective, smart speakers also provide recommendations of products and services that may influence the consumer decision-making process. However, previous studies have mainly focused on the adoption of smart speakers, but there is a lack of proper guidelines that help design the way these devices should offer their consumption recommendations. Based on a stimulus-organism-response approach, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Nowadays, hotel, hospitality and travel industry managers face various alternative options concerning new technologies trends that can not only be used as a solution to the coronavirus pandemic, but also to answer associated shifts in consumer behavior, such as voice search and voice control, contactless payments; robots in hotels and restaurants, chatbots; virtual reality; mobile check-in; recognition technology: artificial intelligence (AI), Internet of Things (IoT): augmented reality; cybersecurity and big data [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, hotel, hospitality and travel industry managers face various alternative options concerning new technologies trends that can not only be used as a solution to the coronavirus pandemic, but also to answer associated shifts in consumer behavior, such as voice search and voice control, contactless payments; robots in hotels and restaurants, chatbots; virtual reality; mobile check-in; recognition technology: artificial intelligence (AI), Internet of Things (IoT): augmented reality; cybersecurity and big data [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive response has been considered, since the early years of marketing theory, as a fundamental variable to understand how consumers respond to a stimulus (e.g., advertising or other product/service‐related information; Oliver, 1980; Wirtz et al, 2000). Research in psychology, marketing and tourism demonstrated that cognitive responses also affect a consumer's emotional state, place attachment, satisfaction and behavioral intentions (Bagozzi, 1992; Dillard & Peck, 2000; Lazarus, 1991; Loureiro, Guerreiro, et al, 2021; Romero et al, 2021; Wakefield & Blodgett, 1999; Zheng et al, 2019). In the restaurant sector, Ladhari et al (2008) and Kim and Moon (2009) found that cognitive response to service quality leads to positive emotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research on this subject has also extended the internal states of the organism to include other variables such as cognition, value, emotion and affect (Fiore & Kim, 2007;Lee et al, 2011). Previous research studies have operationalized attitude as the "organism" in the SOR model in multiple contexts (Chen & Huang, 2012;Kaur et al, 2017;Lee et al, 2011;Moon et al, 2018;Romero et al, 2021;Suparno, 2020;Vergura et al, 2020). Through this study, we seek to make a significant contribution to the existing body of knowledge on the SOR model by operationalizing attitude as an emotional state represented by "organism" in the model and seeking to assess the impact of external stimuli on the attitude of a student towards online learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%